THE COVERAGE OF THE IMPORT PROHIBITION OF INDIAN TEA TO THE TURKESTAN REGION IN THE ARCHIVAL DOCUMENTS (XIX CENTURY 70-IES) - Rakhima Ruskulovna Alimova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article is devoted to cover the issues of prevention of the importation of English-Indian teas into the Turkestan territory in the 70-ies of the XIX century. In this regard, the adoption of regulations prohibiting the entry of English teas into the territory of Turkestan by the Russian Empire and the Turkestan governor’s office and the policy carried out in its implementation are analyzed. Several experts have been sent to the provinces of the region to develop measures to prevent the transportation of Indo-English teas through Bukhara in the territory of the Turkestan generalgovernorship. Their investigations and research works were focused on finding ways of Indian teas coming in from Bukhara, the pricing of the incoming teas, and the amount of tax that was applied to them. These issues are reflected in the documents stored in the funds of the National Archive of Uzbekistan. The materials of the activities carried out in the collected volumes of funds I-1, I-17 of the Turkic general-governorship of the archive have been preserved to establish control over the import of Indian tea and other products of manufacture from the countries of the army into the country. In particular, in the funds, the newspaper editor-in-chief "Turkestanskie Vedomosti" assistant N.A. Maev was sent on a trip to the emirate of Bukhara for tea trade inspection in the Bukhara Khanate, several documents will be analyzed on the issues of improving tea trade in the Turkestan region, as well as a trip report to Turkestan governor-adjutant general Fon-Kaufman